Sign language : my first 100 words - Nelson, Michiyo (New York : Scholastic, 2008)
Featuring illustrations and a simple kid-friendly design, this reference book for the youngest readers makes learning sign language fun and easy.
Family -- Home -- Food -- Colors -- Animals -- Neighborhood -- School -- Sports -- People -- Feelings -- Conversation -- Numbers -- The alphabet.
Includes index.
Keywords: American Sign Language -- Juvenile literature; Deaf -- Means of communication -- United States -- Juvenile literature